The Intersection of Culture and Science in South African Traditional Medicine. - Sobiecki, Jean-Francois (Indo-Pacific Journal of Phenomenology, 2014)
Traditional African medicine often carries with it a perception and stigma of being irrational and ungrounded in scientific method in academia. One reason for this common prejudicial view of traditional African medicine is the failure to effectively interpret African traditional medicine concepts, as these are often metaphorical descriptions of the biological and psychological effects of plants or combinations of them used in the traditional medicine preparations. When translated into other languages such as English, these metaphorical descriptions of medicinal plant use can seem to incorrectly reflect mysticism and/or superstition with no scientific basis. This difficulty in interpreting cultural descriptions of medical phenomena, together with the fact that there are hardly any academic papers engaging the science of South African traditional medicine in the biological sciences, is an indication of the disconnection between the humanities studies and the biomedical studies of South African traditional medicine. This paper investigates some popular examples of spiritual plant use in traditional South African medicine using phytopharmacological studies together with anthropological fieldwork methods, demonstrating the empirical basis for use of some plants in divination (by producing clarity of thought or dreams). The examples also reveal the phytochemical and biomedical foundations of the South Bantu speaking traditional healers' explanations of why and how various spiritually used plants have medicinal value. The challenge for scientists (such as botanists) is to effectively translate and interpret cultural and language based descriptions of spiritual medicinal plant use made by indigenous peoples while recognizing and discarding cultural prejudices that prevent a more comprehensive and integrated understanding of the science that intersects and forms the basis of many, though not all, cultural healing practices.